2011
DOI: 10.1158/0008-5472.can-11-1895
|View full text |Cite
|
Sign up to set email alerts
|

Smad7 Expression in T cells Prevents Colitis-Associated Cancer

Abstract: Patients with inflammatory bowel disease (IBD) have an increased risk of developing colorectal cancer due to chronic inflammation. In IBD, chronic inflammation relies upon a TGFb signaling blockade, but its precise mechanistic relationship to colitis-associated colorectal cancer (CAC) remains unclear. In this study, we investigated the role of the TGFb signaling inhibitor Smad7 in CAC pathogenesis. In human colonic specimens, Smad7 was downregulated in CD4 þ T cells located in the lamina propria of patients wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 45 publications
3
47
0
Order By: Relevance
“…This observation suggests that NFATc2-dependent IL-21 may play an important role in the local environment of developing tumors. However, it should be noted that NFATc2 deficiency did not abrogate proinflammatory cytokine production in general, as other cytokines with important functions in colorectal tumorigenesis such as TNF and IFN-g (35,36) were not affected by the absence of NFATc2. With regard to the production of IL-17A, an important tumor-regulating cytokine (37,38), no changes were observed between lamina propria cells from NFATc2-KO and wild-type mice suggesting that this cytokine does not play a major role in controlling NFATc2-dependent tumor growth.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This observation suggests that NFATc2-dependent IL-21 may play an important role in the local environment of developing tumors. However, it should be noted that NFATc2 deficiency did not abrogate proinflammatory cytokine production in general, as other cytokines with important functions in colorectal tumorigenesis such as TNF and IFN-g (35,36) were not affected by the absence of NFATc2. With regard to the production of IL-17A, an important tumor-regulating cytokine (37,38), no changes were observed between lamina propria cells from NFATc2-KO and wild-type mice suggesting that this cytokine does not play a major role in controlling NFATc2-dependent tumor growth.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, it has been shown that cytokines control tumorigenesis (32,35,36). Interestingly, the transcription factor NFATc2 influences proinflammatory cytokines such as IL-21 that may contribute to carcinogenesis by regulating tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Boulay et al (2003) found that CRC patients with deletion of SMAD7 had a favorable clinical outcome compared with patients with SMAD7 amplification (Boulay et al, 2003), and Halder et al reported that SMAD7-overexpressing FET cells show aggressive colony formation on soft agar and increased tumorigenicity in vivo compared with control FET cells (Halder et al, 2005). In contrast above finding, the opposing role of SMAD7 in the control of sporadic and colitis-associated CRC has been reported by one study in which they showed that over-expression of SMAD7 in T cells associates with severe colitis and reduces the growth of colitis-associated CRC (Rizzo et al, 2011). Therefore, further research on the functionality of SMAD7 variants would be needed to better understand the observed associations.…”
Section: Discussionmentioning
confidence: 95%
“…In transgenic colitis mice, protection from colonic tumors was associated with increased accumulation of cytotoxic CD8 ϩ and natural killer T cells in peritumoral areas (30). CD8 ϩ T-cell deficiency has been suggested as part of the unifying hypothesis for autoimmunity (31).…”
Section: Discussionmentioning
confidence: 99%